Pengaruh Pendidikan, Gaya Hidup, Literasi Keuangan Terhadap Pengelolaan Keuangan Dosen Muda Di Jabodetabek - Rizka Mukhlisiah (IJAcc, 2023)
The economy has quite an important influence in a country, where financial management plays a role in supporting economic success. The management of state finances and the management of individual public finances will play a very important role in achieving the goal of achieving prosperity. The goal of working people is, of course, for a prosperous life both in the present and in the future. However, if uncontrolled expenses will lead to an unhealthy life, for this reason, good financial management is needed so that the goal of a prosperous life can be achieved. The development of financial management is initiated by the existence of a person's behavior in the decision-making process. The purpose of this study was to determine the effect of education, lifestyle, financial literacy on financial management. The object of this research is young lecturers who work in JABODETABEK as the population. The selection of data samples was determined using the porposive sampling method. The results of this study indicate that education has no effect on financial management, lifestyle has no effect on financial management, financial literacy has an effect on financial management.